Phony peach disease: past and present impact on the peach industry in the southeastern U.S.A - Kendall A. Johnson; Clive H. Bock; Phillip M. Brannen (CABI Agriculture and Bioscience)
Abstract Background Phony peach disease (PPD) is caused by the plant pathogenic bacterium Xylella fastidiosa subsp. multiplex (Xfm). Historically, the disease has caused severe yield loss in Georgia and elsewhere in the southeastern United States, with millions of PPD trees being removed from peach orchards over the last century. The disease remains a production constraint, and management options are few. Limited research has been conducted on PPD since the 1980s, but the advent of new technologies offers the opportunity for new, foundational research to form a basis for informed management of PPD in the U.S. Furthermore, considering the global threat of Xylella to many plant species, preventing import of Xfm to other regions, particularly where peach is grown, should be considered an important phytosanitary endeavor. Main topics We review PPD, its history and impact on peach production, and the eradication efforts that were conducted for 42 years. Additionally, we review the current knowledge of the pathogen, Xfm, and how that knowledge relates to our understanding of the peach—Xylella pathosystem, including the epidemiology of the disease and consideration of the vectors. Methods used to detect the pathogen in peach are discussed, and ramifications of detection in relation to management and control of PPD are considered. Control options for PPD are limited. Our current knowledge of the pathogen diversity and disease epidemiology are described, and based on this, some potential areas for future research are also considered. Conclusion There is a lack of recent foundational research on PPD and the associated strain of Xfm. More research is needed to reduce the impact of this pathogen on peach production in the southeastern U.S., and, should it spread internationally, wherever peaches are grown.